2022
DOI: 10.1002/mrm.29161
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating diffusion dispersion across an extended range of b‐values and frequencies: Exploiting gap‐filled OGSE shapes, strong gradients, and spiral readouts

Abstract: To address the long echo times and relatively weak diffusion sensitization that typically limit oscillating gradient spin-echo (OGSE) experiments, an OGSE implementation combining spiral readouts, gap-filled oscillating gradient shapes providing stronger diffusion encoding, and a high-performance gradient system is developed here and utilized to investigate the tradeoff between b-value and maximum OGSE frequency in measurements of diffusion dispersion (i.e., the frequency dependence of diffusivity) in the in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Experimentally, the ∆ D maps demonstrate comparable diffusion dispersion to previously reported studies 5,17,42 . The ∆ K maps exhibit distinct contrast from ∆ D , with larger magnitudes qualitatively observed in white matter relative to gray matter (Figure 4 and Supporting Information Figure S5).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Experimentally, the ∆ D maps demonstrate comparable diffusion dispersion to previously reported studies 5,17,42 . The ∆ K maps exhibit distinct contrast from ∆ D , with larger magnitudes qualitatively observed in white matter relative to gray matter (Figure 4 and Supporting Information Figure S5).…”
Section: Discussionsupporting
confidence: 79%
“…Our technique will significantly benefit from the continued evolution of high‐performance gradients whereby higher gradient amplitudes will offset the reduced b ‐value while still yielding shorter TEs. Additionally, FTB oscillating gradients can also be used in combination with recent advances in OGSE optimization such as the gradient and spin‐echo technique presented by Wu et al, 40 or spiral readouts 41 as demonstrated by Michael et al, 42 to further improve image and map quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-dependent diffusivity of human white matter and gray matter at short diffusion time regimes have been measured in recent years. [30][31][32] ADC or mean diffusivity (MD) has been described by power-law with the diffusion-weighted signal (normalized to b = 0 signal) expressed as:…”
Section: Diffusion Time-dependency Of Human White Matter and Gray Mattermentioning
confidence: 99%
“…The measured ADC (f ) or MD (f ) at OGSE frequencies of 0-120 Hz was reported to fit to a power 𝜃 of 0.5 or 1, a D 0 ranging from 0.6 to 1.2 μm 2 /ms, and a 𝛬 ranging from 2 to 15 μm 2 /s 0.5 (or μm 2 /s) in previous studies. [30][31][32] Figure 1E shows the simulation of ADC (f ) ADC (0 Hz) at f of 0-120 Hz, based on the reported time-dependent diffusivities in human white matter and gray matter. [30][31][32] Compared to solid tumor with high f IN (Figure 1C), ADC (f ) ADC (0 Hz) of white matter and gray matter is smaller.…”
Section: Diffusion Time-dependency Of Human White Matter and Gray Mattermentioning
confidence: 99%